"And So To Work" Exhibition, 1947 (1947)
1947 1945-1960 ""And So To Work" Exhibition, 1947" [HFR0135], 1947 At the end of the war, there were large numbers of people with serious disabilities looking for work. The Government tried to encourage employers to follow the requirements of the 1944 Disabled Persons (Employment) Act by organising this exhibition in Oxford Street, London in January-February 1947. Dozens of workers with a range of disabilities were shown undertaking a wide range of skilled trades.